Am I Way Wrong on this One? On the Multiple Semantic Sources and Paths of Development of the Amplifier Way in American English - Hélène Margerie (Lexis: Journal in English Lexicology)
This article explores the diachronic semantic development of the intensifier way in American English. It has been claimed in the literature that the intensifying function of way derives from the use of spatial adverbial (a)way, but I propose that this may not be the only semantic source involved. This assumption is based on an examination of corpus data extracted from the Corpus of Historical American English. By suggesting that the high degree meaning of way originates from several source constructions, this article contrasts with most case studies on language change which generally focus on just one construction. It is also argued that several mechanisms or causes of semantic change may have played a part in the shift to intensifier function, i.e. metaphorization, pragmatic inferencing and analogization, motivated by semantically related constructions, most prominently the degree modifier construction . A Diachronic Construction Grammar approach will highlight the importance of the architecture of grammar in the process of constructionalization which demands paying attention to constructions at various levels of schematicity to understand the semantic change under study here.